Análises de manifestações patológicas encontradas em edifícios de Belo Horizonte e Nova Lima com até 30 anos de idade - Geovana Chaves Lisboa Saliba (2022)
Currently, pathological manifestations such as exposure and reinforcement corrosion of reinforced concrete, concrete carbonation, fissures, cracks, infiltrations, coating mortar dustiness, differential settlements, drainage system and waterproofing deficiency, are easily found in several buildings. The objective of this work is to identify, determine the origin and analyze the main and most frequent pathological manifestations found in a sample of buildings in Belo Horizonte and Nova Lima with up to 30 years of age, based on a survey carried out with expert professionals, who work in the region. The research included 114 buildings, which will allow the mapping of the main pathological manifestations found, their origin and frequency, also associating age, location, type of building structure and constructive standard. With this, being able to demonstrate the situation of buildings and standard as the consequences of non-compliance with recommended practices by technical standards, which could be avoided if design/execution is correlated with pathological manifestation.